Multi-Label Learning on Tensor Product Graph - Jiang, Jonathan (Proceedings of the AAAI Conference on Artificial Intelligence, 2021)
A large family of graph-based semi-supervised algorithms have been developed intuitively and pragmatically for the multi-label learning problem. These methods, however, only implicitly exploited the label correlation, as either part of graph weight or an additional constraint, to improve overall classification performance. Despite their seemingly quite different formulations, we show that all existing approaches can be uniformly referred to as a Label Propagation (LP) or Random Walk with Restart (RWR) on a Cartesian Product Graph (CPG). Inspired by this discovery, we introduce a new framework for multi-label classification task, employing the Tensor Product Graph (TPG) — the tensor product of the data graph with the class (label) graph — in which not only the intra-class but also the inter-class associations are explicitly represented as weighted edges among graph vertices. In stead of computing directly on TPG, we derive an iterative algorithm, which is guaranteed to converge and with the same computational complexity and the same amount of storage as the standard label propagation on the original data graph. Applications to four benchmark multi-label data sets illustrate that our method outperforms several state-of-the-art approaches.